Nesting behaviour and development of New Zealand falcons (falco novaeseelandiae) in a plantation forest - Holland JD; Thomas A; Minot E (The Ornithological Society of New Zealand)
The breeding behaviour and development of New Zealand falcons (Falco novaeseelandiae) were recorded at 2 nests in Kaingaroa Forest during a 4-month period up to 2 March 2007. This covered the later part of incubation, and the entire nestling and early post-fledging periods. Incubation was shared between parents; the male primarily incubated the eggs, during which time the female hunted. The male only provided occasional prey for the female. Brooding by both parents was intensive for the first 6 days and then gradually declined until the chicks reached 14 days old at which point it ceased. Assisted feeding of the chicks was almost always undertaken by the female. The male’s primary role during the nestling period was prey delivery. During the early nestling period the female spent the majority of the time brooding chicks before shifting to hunting for the young.
Keywords: New Zealand falcon; Falco novaeseelandiae; nest behaviour; pine plantation forest; 0608 Zoology